PSIKOTERAPI ISLAM DAN IMPLIKASINYA DALAM BIMBINGAN DAN KONSELING - Seprianto, Seprianto; Warsah, Idi; Purnama, Dewi (MUHAFADZAH: Jurnal Ilmiah Bimbingan dan Konseling Islam, 2022)
Islamic psychotherapy is a process of healing or treatment given to clients by a professional counselor or therapist using a psychological approach, the Koran and hadith, with the aim of helping clients overcome their challenges. both mental problems, spiritual problems (religion), moral problems, and physical problems. Increasing the client's faith and worship, learning and practicing the Qur'an, psychological therapy through prayer, zakat, fasting, pilgrimage, patience, istighfar, and repentance, as well as therapy through dhikr and prayer are all methods that can be used in psychotherapy. The implication in Guidance and Counseling needs to help clients' various life problems, Psychotherapy is the main focus of this research. The type of this research used is library research. The content analysis method was used in this study to analyze the data. Valid conclusions can be drawn from this analysis, which can be double-checked in context. In this analysis, it will be carried out by selecting, comparing and combining some of the data that has been obtained from previous relevant studies. The results and conclusions in this study are Islamic psychotherapy in guidance and counseling is a process of healing or treatment carried out by counselors (therapists) who are professionals in their fields to counselees or clients through a psychological approach, the Koran and hadith.